If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -1x = x Solving 4 + -1x = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 4 + -1x + -1x = x + -1x Combine like terms: -1x + -1x = -2x 4 + -2x = x + -1x Combine like terms: x + -1x = 0 4 + -2x = 0 Add '-4' to each side of the equation. 4 + -4 + -2x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -2x = 0 + -4 -2x = 0 + -4 Combine like terms: 0 + -4 = -4 -2x = -4 Divide each side by '-2'. x = 2 Simplifying x = 2
| x^5+x^2+x=0 | | 8x+4=5(x+2) | | 9.40dm=hm | | X-2x=3x-20 | | 6(7+2x)-8x-(y+4)=12 | | 7x+8-x+7=3x+24 | | (x-3)2=15 | | -24=t-29 | | 40-13x=1 | | x^2-4x+6y+10=0 | | 8.5(13x-27)=-119 | | 2(1y-4)=-4y+10 | | 2(3x+9)=-36 | | 36z^2+9z+15=0 | | -11=2+y | | 5(u+4)=9u+32 | | 12x^2=4x | | 24+a=-14 | | 6-6x=10-8x | | -8x+95=-425 | | -14+p=7 | | 4=-n-n | | 18=-8+n | | 16+n/8=26 | | 3(2v+14)=-15v | | y^2+11y+62=0 | | 3(3j+15)=-3(11-5j) | | -4(4w+20)-15=-6w+17+18 | | 3=3(2q-7) | | (98x+27)9+5x-1=6(x+23) | | 9(2k+1)=-4+19k | | -3(-14q-19)-15q=-16-8+18q |